Estimation of Aflatoxin M1 Exposure through Consumption of Various Dairy Milk Products in Yogyakarta, Indonesia (ESTIMASI PAPARAN AFLATOKSIN M1 MELALUI KONSUMSI BERBAGAI PRODUK SUSU DI YOGYAKARTA, INDONESIA) - Sumantri, Ika; Purwanti, Fitri; Nuryono, Nuryono; Agus, Ali (Jurnal Veteriner; Vol 20 No 1 (2019), 2019)
This study was conducted to investigate the occurrence of aflatoxin M1 (AFM1) in various milk products marketed in Yogyakarta Province (Indonesia) and to estimate the exposure of aflatoxin through contaminated milk consumption. Fresh milk (n=20), pasteurized milk (n=16), and recombined milk products (n=6) were sampled for AFM1 concentration testing by a competitive ELISA test using ELISA kit for AFM1 assay. A survey was conducted to interview consumers (n=88) on milk consumption habit (milk type and amount of consumption). ELISA assays showed 92.5% of samples werecontaminated with AFM1 in a range of 24-570 ng/L (average: 216 ng/L). The highest average AFM1 concentration was detected in pasteurized milk sample (244 ng/L), followed by fresh milk (219 ng/L), and the lowest was in recombined milk sample (131 ng/L). However, 100% of recombined milk samples had AFM1 concentration >50-500 ng/L. Thus, recombined milk product was most likely the main source of AFM1 intake due to its high daily consumption in all age groups. Based on AFM1 levels found in milk and consumption of corresponding milk sample, it was estimated that the overall AFM1 exposure ranges from 1.23 ng/kg body weight/day (in 6-15 year-old children) up to 5.26 ng/kg body weight/day (in 3-5 year-old children). In conclusion, this study revealed high occurrences of AFM1 dairy milk marketed in Yogyakarta. Although levels of AFM1 contamination were in Indonesian regulatory limit, high exposure of aflatoxin found in all age groups of consumer. Thus, this preliminary study provides evidence that AFM1 contaminated milk is a serious public health hazard in Indonesia.